Features in distributions of secondary particles in interactions of nuclei - Fedosimova, A.I.; Abishev, M.E.; Kozhamkulov, T.A.; Lebedev, I.A. (Recent Contributions to Physics, 2019)
The paper presents the results of an analysis of the interactions of heavy lead nuclei 208Pb at energy of 158 AGeV and gold nuclei 197Au at energy of 10.7 AGeV with photoemulsion nuclei Em. The results were processed using the Hurst method. The total ensemble of events has been divided into two classes dependending on the Hurst index h, which are called events of explosive and cascade-evaporation types. In explosive events, interactions have been discovered in which secondary particles are emitted at large angles. The analysis of this effect depending on the energy of the projectile nucleus is presented. Gold and lead nuclei have approximately the same mass, but they differ in energy by almost 15 times. However, the relative number of explosive events is almost the same. In the Au + Em interactions 64.7% of explosive events are observed. Moreover, 8.1% of the interactions are events of complete destruction which have no fragments of the target nucleus. There are 59.7% of explosive type events and 8.9% of complete destruction events in Pb + Em interactions. However, the number of events with large values ​​of the mean pseudorapidity distribution <h> differs significantly. In Au + Em interactions, 35.6% of the events are explosive events with large <h> values. There are only 8.4% of such events in Pb + Em.